The effects of three physical modifications on the structural and functional characteristics of soluble dietary fibers: comparison among ultrasound, ball milling and cold plasma treatments - Yijie Shi; Chengcheng Liu; Wenyue Li; Fenyi Min; Junwei Cao; Ruibo Cao; Mengqing Li; Xuebo Liu; Lijun Sun (Ultrasonics Sonochemistry)
This work studied three physical modifications, including ultrasound (US), ball-milling (BM), and cold plasma (CP) on Flammulina velutipes soluble dietary fibres (FV-SDF) regarding the structural and functional properties. Interestingly, BM was indicated to cause the most changes in SDF molecular structures among three modifications, refining surface morphology, significantly decreasing molecular weight, and exposing polar functional groups. This contributed to the greatly modified solubility and decreased viscosity of FV-SDF treated by BM that exerted a strong shear force onto SDF. By contrast, in CP treatment, high-energy particles in plasma stroke on FV-SDF powder, only causing the etching effect on SDF surface, instead of intramolecular regions. This caused the hardly changed molecular weight and slightly decreased viscosity of FV-SDF treated by CP. On the other hand, in US treatment, a mass of bubbles obtained enough vibration energy and then broke, causing cavitation effect, i.e., producing bursting force. As US treatment was performed at the dissolving status, the cavitation effect directly acted in the intramolecular regions of SDF. By this way, the molecular weight of FV-SDF was decreased by ultrasound, which resulted in the decrease in SDF viscosity. Interestingly, the lipolysis process of lipase was significantly retarded by all FV-SDF samples, and this arose from the viscosity characters of the fibres that impacted the direct enzyme-substrate interactions. Conclusively, the above approaches may be selectively applied to modify SDF according to their effects on the structural and functional properties of the fibres, including molecular weight, surface morphology, solubility, viscosity, adsorption capacity, and lipolysis inhibition.